Entomofauna visitante de Stenolobium stans (Juss.) Seem (Bignoniaceae), durante seu período de floração - Dutra, João C. S. [UNESP]; Machado, Vera L. L. [UNESP] (My University, 2001)
Studies on the different ways of reproduction of Stenolobium stans (Juss.) Seem and on the diversity, frequency and constancy of flower-visiting insects at different hours were carried out during four years. The S. stans flowers open between 5 and 6 am during 3 to 8h, with 90% pollen viability. Besides the pollen, the flower has other features that are attractive to the visiting insects, like osmophores responsible for a sweet odor, ultra-violet reflected light and nectar at 25% of sugar. The plant is autocompatible and reproduces by autogamy, geitonogamy or xenogamy. This behavior demands external pollination and justifies the species to be a serious invasor of grounds and pastures. Large diversity of insects were observed visiting the flowers, with predominance of bees. The pollinators species were Centris collaris Lepeletier, Bombus morio (Swederus), Eulaema nigrita Lepeletier and Epicharis sp. The incidence of native species was lower at the rural area than at the urban one, with predominance of the exotic Apis mellifera L. The environmental factors, mainly temperature, light, relative humidity and wind speed, influenced the foraging activity of the insects.
Flowering entomofauna in Stenolobium stans (Juss.) Seem (Bignoniaceae)
Keywords: Bee; Flower visitor; Flowers; Insecta; Pollination